Quasinormal modes and thermodynamical aspects of the 3D Lifshitz black hole - Cuadros-Melgar, B. (2013)
We consider scalar and spinorial perturbations on a background described by a z = 3 three-dimensional Lifshitz black hole. We obtained the corresponding quasinormal modes which perfectly agree with the analytical result for the quasinormal frequency in the scalar case. The numerical results for the spinorial perturbations reinforce our conclusion on the stability of the model under these perturbations. We also calculate the area spectrum, which prove to be equally spaced, as an application of our results.